Coadministration of bedaquiline and pyrifazimine reduce exposure to toxic metabolite N-desmethyl bedaquiline - Ding, Yangming; Liu, Haiting; Wang, Furun; Fu, Lei; Zhu, Hui; Fu, Shuang; Wang, Ning; Zhuang, Xiaomei; Lu, Yu (Frontiers in Pharmacology, 2023)
A new, effective anti-tuberculosis (TB) regimen containing bedaquiline (BDQ) and pyrifazimine (TBI-166) has been recommended for a phase IIb clinical trial. Preclinical drug-drug interaction (DDI) studies of the combination of BDQ and TBI-166 have been designed to support future clinical trials. In this study, we investigated whether a DDI between BDQ and TBI-166 affects the pharmacokinetics of BDQ. We performed in vitro quantification of the fractional contributions of the fraction of drug metabolism by individual CYP enzymes (fm) of BDQ and the inhibition potency of key metabolic pathways of TBI-166. Furthermore, we conducted an in vivo steady-state pharmacokinetics study in a murine TB model and healthy BALB/c mice. The in vitro fm value indicated that the CYP3A4 pathway contributed more than 75% to BDQ metabolism to N-desmethyl-bedaquiline (M2), and TBI-166 was a moderate (IC50 2.65 µM) potential CYP3A4 inhibitor. Coadministration of BDQ and TBI-166 greatly reduced exposure to metabolite M2 (AUC0-t 76310 vs 115704 h•ng/mL, 66% of BDQ alone), whereas the exposure to BDQ and TBI-166 did not changed. The same trend was observed both in healthy and TB model mice. The plasma concentration of M2 decreased significantly after coadministration of BDQ and TBI-166 and decreased further during treatment in the TB model. In conclusion, our results showed that the combination of BDQ and TBI-166 significantly reduced exposure to the toxic metabolite M2 by inhibiting the activity of the CYP3A4 pathway. The potential safety and efficacy benefits demonstrated by the TB treatment highly suggest that coadministration of BDQ and TBI-166 should be studied further.